The Impact of Spinal Anesthesia in Sitting Versus Lateral Decubitus Positions on Sensory Block Onset and Hemodynamic Stability in Lower Limb Surgeries - Raheel Sajjad; Mukhtiar Ahmad; Muhammad Ashfaq; Zemran Zafar; Abeera Amir; Muhammad Farhan Hassan; Imad Ud Din (Journal of Health, Wellness and Community Research, 2025)
Background: Spinal anesthesia is widely used in lower limb surgeries for its efficacy and safety, particularly in elderly patients. However, the optimal positioning during administration—sitting versus lateral decubitus—remains debated due to its potential impact on block dynamics and hemodynamic stability. Objective: To compare the effects of spinal anesthesia administered in the sitting versus lateral decubitus positions on sensory block onset, hemodynamic parameters, and patient satisfaction in elderly patients undergoing lower limb surgeries. Methods: A descriptive cross-sectional study was conducted across three tertiary hospitals in Lahore over four months, involving 100 ASA I–II patients aged 60 years and above undergoing elective lower limb surgeries. Patients were divided into two equal groups (n=50) based on positioning during spinal anesthesia. Sensory and motor block onset times, systolic blood pressure, heart rate, and patient comfort were recorded and analyzed using independent t-tests and chi-square tests. Results: The lateral group exhibited significantly faster sensory block onset (64.2 ± 7.75 vs. 75.3 ± 10.35 seconds, p<0.001), shorter time to reach maximum block level (6.69 ± 1.33 vs. 8.11 ± 1.41 minutes, p<0.001), and greater hemodynamic stability up to 30 minutes post-induction. Comfort ratings were also significantly higher in the lateral group (24% vs. 4% rated “very comfortable,” p<0.001). Conclusion: Lateral positioning for spinal anesthesia offers superior sensory block dynamics, enhanced hemodynamic stability, and improved patient satisfaction in elderly individuals, supporting its use as a preferred clinical approach in lower limb surgeries.